Quality of care and satisfaction of the outpatient users in a public hospital in Peru - Arévalo-Marcos, Rodolfo A. (2022)
Objective. To determine the relationship between quality of care and users satisfaction in the outpatient clinic of the Daniel Alcides Carrión National Hospital, in Callao (Peru). Methods. The study was quantitative, observational and cross-sectional. The non-probabilistic sample consisted of 100 users. Two scales were applied to measure the quality of care and users satisfaction, which were previously validated and validated. Spearman's rho test was applied in the inferential analysis. Results. The 51% perceived the quality of care to be fair, compared to 39% who considered the quality of care to be good. On the other hand, 39% of the sample was found to be moderately satisfied with the service and 29% was satisfied, but 32% of the sample was also found to be dissatisfied with the service provided by the health personnel. Conclusion. There is a direct relationship between quality of care and users satisfaction in the outpatient clinic of the Daniel Alcides Carrión National Hospital (Spearman's rho of 0.626, significant at 0.001).